Analisis Kinerja Keuangan Sebelum dan Sesudah Merger Pada PT. Bank Syariah Indonesia - Adenan, Moh; Puspita, Desi Dwi Prabaswara; Suparman, Suparman (IJABAH, 2023)
Bank Syariah Indonesia, Bank BSI, is a merger of bank state owned state as Bank Syariah Mandiri, BSM, Bank Negara Indonesia Syariah, BNIS, and Bank Rakyat Indonesia Syariah, BRIS to empower and develop sharia economic ecosystem and national halal industry. This study aims to analyze the differences financial performance before and after merger into BSI. This research utilized descriptive comparative financial ratio as follows Capital Adequacy, CAR, Non-Performing Financing, NPF, Return on Assets, ROA, and Short Term Mismatch, STM. The results concluded that the three banks state banks before the merger had categorized good in capital and asset quality, and after the merger they showed an increase so that their capital and asset quality became very good. The average profitability of Sharia banks before the merger was good, except Bank BSM was still not good, then after merger resulted into Bank BSI categorized better profitability. The liquidity of the three banks before the merger was not good, but after the merger, Bank BSI had increased so that it became very good. So the merger into Bank BSI can increase financial performance.